PERAN KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI SDN KECAMATAN SAMARINDA ILIR TAHUN PELAJARAN 2017/2018 - Nur Agus Salim (PENDAS MAHAKAM: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2018)
with the era of globalization, and the increasingly intense competition in the world of education today Leadership Principals have an important role in the realization of good teacher performance. The principal should pay more attention to the teacher's performance as this is one of the never-ending problems. The principal must have a strong leadership spirit against teachers who have poor performance and impose the sanction that should be. Such assertive action is taken so that the work of teachers in accordance with existing standards, but of course that the work can be perfect should be supported by creating a good working environment, so that teachers do not feel depressed in doing their work, thus there is a mutual relationship between the leadership and subordinates to fill each other as their duties and responsibilities.Keywords: Principal Leadership, Teacher Performance.